An Investigation of Combustion and Performance Characteristics of a Direct Injection Diesel Engine Fuelled With The Blends of 10% Fish Oil Biodiesel and 90% Diesel Fuel - Fatih AKSOY (Gazi Üniversitesi Fen Bilimleri Dergisi, 2019)
In the current study, combustion and performance characteristics of a direct injection diesel engine fuelled with the blends of 10% fish oil biodiesel and 90% diesel fuel were investigated experimentally. For this reason, the test engine was run at 2200 rpm and 3.75, 7.5, 11.25 and 15 Nm engine loads. The variations of in-cylinder pressure, heat release, combustion duration, ignition delay, thermal efficiency and specific fuel consumption were observed. In-cylinder pressure and heat release increased while combustion duration was shortened with fish oil biodiesel. Test results showed that in-cylinder temperature increased with fish oil biodiesel. Indicated mean effective pressure (imep) and indicated thermal efficiency (ITE) decrased owing to lower calorific value of fish oil biodiesel. ITE was determined as 28.27% with diesel whereas 25.58% with B10 at 11.25 Nm engine load. Specific fuel consumption (SFC) was computed as 0.162 kg/kWh with diesel while 0.214 kg/kWh with B10 with the increase of about 32%. Test results showed that the blends of fish oil biodiesel-diesel can be utilized without modifications in diesel engines and combustion characteristics were improved.